2019
DOI: 10.1111/jcmm.14758
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics of epicardial adipose tissue in patients with heart failure

Abstract: Epicardial adipose tissue (EAT) is a metabolically active visceral fat depot closely linked to the pathogenesis of heart failure (HF). But the molecular signatures related to the mechanism of HF have not been systematically explored. Here, we present comprehensive proteomic analysis of EAT in HF patients and non‐HF patients as controls. A total of 771 proteins were identified in liquid chromatography‐tandem mass spectrometry experiments. Amongst them, 17 increased in abundance in HF and seven decreased. They w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 32 publications
0
28
0
Order By: Relevance
“…In circulating plasma, the level of SERPINA3 in the HF group was confirmed significant increase by ELISA analysis. These results suggested that SERPINA3 might play an important role in the progression of HF ( Zhao et al, 2020 ). Asakura and Kitakaze (2009) proved that SERPINA3 might become novel diagnostic and therapeutic targets linked to the pathophysiology of HF using seven microarray datasets previously reported.…”
Section: Discussionmentioning
confidence: 90%
“…In circulating plasma, the level of SERPINA3 in the HF group was confirmed significant increase by ELISA analysis. These results suggested that SERPINA3 might play an important role in the progression of HF ( Zhao et al, 2020 ). Asakura and Kitakaze (2009) proved that SERPINA3 might become novel diagnostic and therapeutic targets linked to the pathophysiology of HF using seven microarray datasets previously reported.…”
Section: Discussionmentioning
confidence: 90%
“…Several studies have examined MS/MS proteomics to evaluate the disease state of HF ( 9 , 44 , 45 , 46 , 47 ). In a study of ischemic cardiomyopathy (ICM), Yi et al.…”
Section: Current Use Of Proteomics In Hf Studiesmentioning
confidence: 99%
“…Proteins are the end products of gene expression and can better and directly illuminate the processes behind the manifestation of diseases. Comparative proteomics methods are widely used to analyze the relative amounts of proteins in two or more biological samples to screen for biomarker proteins for judgment and prognosis [12][13][14]. Label-free quantitative (LFQ) analysis is one of proteomics methods [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Comparative proteomics methods are widely used to analyze the relative amounts of proteins in two or more biological samples to screen for biomarker proteins for judgment and prognosis [12][13][14]. Label-free quantitative (LFQ) analysis is one of proteomics methods [12,13]. Compared to label quantitative analysis, LFQ can avoid the drawbacks of labeling quanti cation techniques: additional sample processing, sample complexity caused by incomplete labeling, di culty in detecting low abundance peptides, limited number of labeled samples, etc [13,15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation